Intime Beziehungen. Ästhetik und Theorien der Sexualität um 1968 - Weder, Christine (Wallstein Verlag, 2016)
The author compares theories of sexality and theories of aesthetics around 1968 and find out that there is a strong relation between them. So she states that there is not only a tendency of a politization of aesthetics at that time, but also a tendency to be sexually connotated or even sexualized.